2016 International Conference of the Biometrics Special Interest Group (BIOSIG) 2016
DOI: 10.1109/biosig.2016.7736929
|View full text |Cite
|
Sign up to set email alerts
|

Isolating Iris Template Ageing in a Semi-Controlled Environment

Abstract: The ageing of the iris and its influence on recognition performance is a hotly debated topic. Template ageing in iris biometrics is often attributed to changes during acquisition rather than the natural ageing of the iris. In this paper, we attempt to isolate template ageing effects in iris recognition by using a semi-controlled environment (selecting a subset from a larger database) and controlling as many factors as possible in the biometric tool-chain. This includes manual segmentation and the use of a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Especially, at an age over 6 months this becomes crucial as the pattern changes significantly at this age. This is also an interesting result with regard to the biometry of the human iris, since the human iris shows ageing effects, although the severity of the impact is controversial (see [24]). The fish under study have now also shown an ageing effect, which can much more readily observed and researched owing to the faster life cycle of the Atlantic salmon.…”
Section: Resultsmentioning
confidence: 89%
“…Especially, at an age over 6 months this becomes crucial as the pattern changes significantly at this age. This is also an interesting result with regard to the biometry of the human iris, since the human iris shows ageing effects, although the severity of the impact is controversial (see [24]). The fish under study have now also shown an ageing effect, which can much more readily observed and researched owing to the faster life cycle of the Atlantic salmon.…”
Section: Resultsmentioning
confidence: 89%
“…NIST's IREX VI report, however, states the contrary (Grother et al, 2013), and was later criticized by Bowyer (Bowyer and Ortiz, 2013), and a response to that critique was also published (Grother et al, 2015). Recently, more researchers have made efforts to better understand the non-stationarity of templates, namely by isolating as many factors as possible (Hofbauer et al, 2016), studying the impact of segmentation quality (Wild et al, 2015), but also the influence of sensor aging (Bergmuller et al, 2014). This shows that despite many research efforts having been put into solving these issues, template aging still presents many challenges, and new solutions and experimental methodologies are much welcome.…”
Section: Iris Template Non-stationaritymentioning
confidence: 99%
“…The first is template aging. Template aging is defined as the increase in error rates caused by time-related changes, meaning changes in the biometric pattern, the presentation of the pattern and the sensor [1], [2]. Aging affects the human body and the acquisition sensor.…”
Section: Introductionmentioning
confidence: 99%